Refugees and regional security in South Asia - Muni, S. D.; Baral, Lok Raj, 1941-; Regional Centre for Strategic Studies (Colombo, Sri Lanka) (Delhi, India : Konark Publishers, 1996)
Contains papers presented at a seminar.
"Under the auspices of Regional Centre for Strategic Studies, Colombo, Sri Lanka."
Includes bibliographical references and index.
Keywords: Refugees -- South Asia; South Asia -- Foreign relations; South Asia -- Politics and government; South Asia -- Ethnic relations